Sustainable manufacture and application of biochar to improve soil properties and remediate soil contaminated with organic impurities: a systematic review - Rizwan, Muhammad; Murtaza, Ghulam; Zulfiqar, Faisal; Moosa, Anam; Iqbal, Rashid; Ahmed, Zeeshan; Irshad, Sana; Khan, Imran; Li, Tonghao; Chen, Jiefeng; Zhang, Mingguang; Siddique, Kadambot H. M.; et al. (Frontiers in Environmental Science, 2023)
Biochar production and application has have become progressively increasingly popular in the past 15fifteen15 years. Biochar, derived obtained from diversevarious types of biomassbiomass types, is an exceptionallyoffers a rich wellspring of carbon source created through manufactured from biomass employing thermal combustion.; bBiochar production primarilycreation depends on pyrolysis conditions and feedstock types. This review focuses on the multifaceted aspects of biochar, encompassing Study on the biochar was deliberated involving its production and application, as a source of bio-economy and soil soil remediationdecontamination. Hhydrothermal carbonization, gasification, and pyrolysis temperatures arewere debated in this review in biochar production and its role in the bioeconomy and soil remediationcreating biochar for the remediation of soils. Biochar has yieldedve built valuable discoveries insights, notably infor decreasing soil nutrients leaching damages, reducing curbing global warming and greenhouse gases (GHGs) emissions, reducing the bioavailability of environmental pollutants, Sequester sequestering carbon (C) into soils, and enhancing the agricultural productivity. of agricultural sector and cConsequently, it has becoming emerged as a valuable product commodity for themaintaining bio-economy, which involves harnessing. Bio-economy intimates the exploitation and exploration of bioresources through, which includes the employ ofemploying bioengineering to create form novel economically valuable products of economic worth. The bBiochar is a vendible outputAs a marketable output, biochar, which can be utilized in energy, different manufacturing finds application that can be utilized in energy, diverse biochar-based product manufacturing of various products from biochar, and the agricultureal sectors. ConsequentlyThus, production of the biochar can improve soil'sbiochar production cannot only enhances improve soil quality but also unlocks additionaland give extra opportunities for more revenue streams. This reviewstudy demonstrates underscores the critical role Ssignificance of feedstock selection and pyrolysis conditions for in optimizing potential biochar production. Furthermore, it highlights and this review\ specified that biochar as a sustainable and effective tool for improvingement in various soil types of soils as well as and remediatingon of soil contamination caused byed soil with organic impurities, including such as persistent organic compounds and, antibiotics etc.